Acceptability of bisphosphonates among patients, clinicians and managers: a systematic review and framework synthesis. Issue 11 (3rd November 2020) - Paskins, Zoe; Crawford-Manning, Fay; Cottrell, Elizabeth; Corp, Nadia; Wright, Jenny; Jinks, Clare; Bishop, Simon; Doyle, Alison; Ong, Terence; Gittoes, Neil; Leonardi-Bee, Jo; Langley, Tessa; et al.
Abstract : Objective: To explore the acceptability of different bisphosphonate regimens for the treatment of osteoporosis among patients, clinicians and managers, payers and academics. Design: A systematic review of primary qualitative studies. Seven databases were searched from inception to July 2019. Screening, data extraction and quality assessment of full-articles selected for inclusion were performed independently by two authors. A framework synthesis was applied to extracted data based on the theoretical framework of acceptability (TFA). The TFA includes seven domains relating to sense-making, emotions, opportunity costs, burden, perceived effectiveness, ethicality and self-efficacy. Confidence in synthesis findings was assessed. Setting: Any developed country healthcare setting. Participants: Patients, healthcare professionals, managers, payers and academics. Intervention: Experiences and views of oral and intravenous bisphosphonates. Results: Twenty-five studies were included, mostly describing perceptions of oral bisphosphonates. We identified, with high confidence, how patients and healthcare professionals make sense (coherence) of bisphosphonates by balancing perceptions of need against concerns, how uncertainty prevails about bisphosphonate perceived effectiveness and a number of individual and service factors that have potential to increase self-efficacy in recommending and adhering to bisphosphonates. We identified, with moderate confidence, that bisphosphonate taking induces concern, but has the potential to engender reassurance, and that both side effects and special instructions for taking oral bisphosphonates can result in treatment burden. Finally, we identified with low confidence that multimorbidity plays a role in people's perception of bisphosphonate acceptability. Conclusion: By using the lens of acceptability, our findings demonstrate with high confidence that a theoretically informed, whole-system approach is necessary to both understand and improve adherence. Clinicians and patients need supporting to understand the need for bisphosphonates, and clinicians need to clarify to patients what constitutes bisphosphonate treatment success. Further research is needed to explore perspectives of male patients and those with multimorbidity receiving bisphosphonates, and patients receiving intravenous treatment. PROSPERO registration number: CRD42019143526.